A Conceptual Study on Islamic Banking and Analysing the Possibilities of Imbibing it With Conventional Banking System in India (International Journal of Food and Nutritional Sciences, 2022)
India might be a significant market for Islamic banking institutions because of its huge Islamic population and the idea of interest-free banking, which are the two factors that contribute to the possibility for Islamic banking in India. Nevertheless, a favourable shift in the legislative framework and more awareness among India's Muslim community are still possible. This research examines the fundamental ideas and principles of Islamic finance, as well as the possibilities for Islamic finance in India and the fusion of conventional and Islamic finance. Additionally, this research demonstrates the ways that Islamic banking is financed and outlines its main problems and limitations. According to several studies, India has the potential to become a big market for Islamic banking institutions if the regulatory framework changes favourably and more people in India as a whole become aware of the opportunities. Unfortunately, Islamic banking is perceived in India as a religious philanthropic endeavour limited to the nations economically and socially marginalised Muslim population. This notion has persisted despite years of effective Islamic banking operations and their amazing expansion globally. Islamic banking should be investigated by the RBI and the Ministry of Finance as a potential solution to the microeconomic issues that the Indian people are now facing Islamic banking is currently a household term in the international financial community, with all the necessary components of current banking interest. Economy of India has been expanding, but ironically so has the rate of loan borrowing. The government must work to create an equitable society. The majority of Indians, meanwhile, don't have access to credit. The current financial system does not support safeguarding the interests of any and all demographic groups. In the past several decades, various regions of the world have established the Islamic banking system with regarding to the Shariah law. Islamic banking is a risk-sharing system where risks are shared between the lender and the borrower through partnerships, joint ventures, leases, and sales based on real assets. In contrast to traditional banking, where trading in interest is assumed to be a main product, money is solely believed to be a means of exchange. This project throws a bird eye view on imbibing the Islamic banking concepts with conventional banking system in India.